2019
DOI: 10.1016/j.visres.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The features that control discrimination of an isodipole texture pair

Abstract: Visual features such as edges and corners are carried by high-order statistics. Previous analysis of discrimination of "isodipole" textures, which isolate specific high-order statistics, demonstrates visual sensitivity to these statistics but stops short of analyzing the underlying computations. Here we use a new "texture centroid" paradigm to probe these co mputations. We focus on two canonical isodipole textures, the "even" and "odd" textures: any 2×2 block of even (odd) texture contains an even (odd) number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These suggested that the lower bound on the number of those mechanisms is between 4 and 7 [7]. That being said larger patch sizes than 2×2 seem to be needed to fully explain discrimination of isotrigon textures [16] and their visual salience [2], implying the possible involvement of 5 th and higher-order correlations. As we [6] and others [7] have recognized, considering 2×2 block correlations is related to the Minkowski functionals (MFs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly then, humans and primates have been shown to be acutely sensitive to such correlations in a number of psychophysical [3][4][5][6][7], electrophysiological [8][9][10][11], and brain imaging [12][13][14] studies. A range of synthetic texture stimuli that have well-controlled correlation structure have been designed to probe our sensitivity to such image structure [3,7,15,16]. It has also been reported that the image structure that makes some of these synthetic textures visually salient also makes natural textures salient, and that this structure represents non-redundant correlation content in these images [2].…”
Section: Introductionmentioning
confidence: 99%